An integrated care pathway for total knee arthroplasty in a private hospital in South Africa - Smith, Petrus Johannes (My University, 2017)
Integrated care pathways (ICP’s), for total knee arthroplasty (TKA) and partial knee arthroplasty (PKA) have been used successfully in the last two decades. ICP’s have been known among other terms as ‘critical care pathways’, ‘algorithms of care’, ‘patient care pathways’, ‘collaborative care pathways’. The main aims of an ICP is that it coordinates the efforts of the members of the multi-disciplinary team through the alignment of the objectives of patient care processes. It improves outcomes of care and patient satisfaction is supported by comprehensive patient information provision both verbally and written. It is generally accepted that ICPs have an impact on the length of stay of patients in hospital, thus further enhancing the feeling of wellbeing of patients but also significantly contributing to the cost of surgery, care and rehabilitation. (Schuur et al, 2011).
A dissertation Master of Science in nursing education
Keywords: Knee Arthroplasty; Knee; Arthroplasty